Intrapericardial gossypiboma: Rare cause of intrathoracic mass. (2018) - Kumar, Anil; Paswan, Shiv Shankar; Prashad, Rajinder; Kumari, Rekha; Kumar, Bindey
Highlights: Intrapericardiac gossypiboma is an extremely rare condition. CT also may be failed to confirm the diagnosis of gossypiboma. Re-exploration is the ideal approach. Proper sponge counting is the best way to prevent the occurrence of gossypiboma. Abstract: Introduction: Gossypiboma is a retained surgical sponge inside our body after surgical intervention. It is most commonly found in abdominal cavity. Its occurrence in thoracic cavity as intrapericardial gossypiboma is extremely rare. Presentation of case: We present a 25 year old male with complaint of chest pain for 1 year. He had a history of total correction of Tetralogy of fallot 14 years back, at another hospital. On clinical examination and investigations including contrast enhanced computed tomography (CECT) of thorax; diagnosis of right anterior mediastinal mass of germ cell tumor was made and planned for thoracotomy. On exploration, the gauze piece of 31 cm was removed from the pericardial mass and a final diagnosis of gossypiboma was made. Discussion: Although gossypibomas are commonly reported in abdominal and pelvic surgery but a prolonged operative time, untrained staff, poor communication in sponge count may favour the occurrence in thoracic cavity. A patient with intrathoracic gossypiboma usually presents with chest pain, dyspnoea, thoracic mass or fever. CECT and Magnetic resonance Imaging (MRI) are useful imaging modality in such cases. Surgical exploration with histopathological examination confirms the diagnosis of gossypiboma. Conclusion: In a postoperative patient who presents with chest pain and intrathoracic mass, gossypiboma should be a differential diagnosis even it is rare to occur in thorax.